A comprehensive analysis of peptides presented by HLA‐A1. Issue 6 (16th April 2015) - Giam, K.; Ayala‐Perez, R.; Illing, P. T.; Schittenhelm, R. B.; Croft, N. P.; Purcell, A. W.; Dudek, N. L.
Abstract Human leukocyte antigen (HLA)‐A1 is one of the most common Caucasian HLA‐A alleles. Here, we describe the comprehensive analysis of the HLA‐A*01:01 ligand repertoire with the identification of 4735 naturally processed and presented peptides derived from 2477 source proteins. We found HLA‐A*01:01 bound an equivalent number of ligands of 9 or 10 amino acids in length as well as being remarkably tolerant of even longer peptides. Indeed close to half of the HLA‐A1 bound peptides identified ranged between 11 and 13 amino acids in length. These longer peptides contained the strong canonical motif of and acidic E/D residue at position 3 (P3) and Y at the C‐terminus (CΩ), a motif that was still apparent in peptides of up to 18 amino acids in length. The identification of this large database of natural ligands will facilitate the refinement of predictive algorithms particularly with respect to longer peptide ligands.